The externalist’s guide to fishing for compliments - Salow, B (Oxford University Press, 2017)
Suppose you’d like to believe that p (for example, that you are popular), whether or not it’s true. What can you do to help? A natural initial thought is that you could engage in Intentionally Biased Inquiry: you could look into whether p, but do so in a way that you expect to predominantly yield evidence in favour of p. This paper hopes to do two things. The first is to argue that this initial thought is mistaken: intentionally biased inquiry is impossible. The second is to show that reflections on intentionally biased inquiry strongly support a controversial ‘access’ principle which states that, for all p, if p is (not) part of our evidence, then that p is (not) part of our evidence is itself part of our evidence.